Natural and lab-derived microbiomes differentially shape stressor interaction patterns of Daphnia magna - Houwenhuyse, Shira; Bulteel, Lore; Vanoverberghe, Isabel; Krzynowek, Anna; Van de Maele; Marlies; Coone, Manon; Van den Wyngaert; Silke; Sinnesael, Arne; Stoks, Robby; Decaestecker, Ellen (Oxford University Press (OUP), 2025)
Organisms are facing multiple, potentially interacting stressors in natural populations. The ability of populations coping with combined stressors depends on their tolerance to individual stressors and how stressors interact, which may not be correctly captured in controlled laboratory settings. One reason for this is that the microbial communities in laboratory settings often differ from the natural environment, which could result in different stressor responses and interaction patterns. In this study, we investigated the impact of single and combined exposure to a toxic cyanobacterium and an oomycete parasite on the performance of three Daphnia magna genotypes. Daphnia individuals were sterilized and subsequently exposed to a natural or a laboratory-derived microbial inoculum. Survival, reproduction and body size were monitored, and gut microbiomes were characterized. Our study confirmed that natural and laboratory microbial inocula and gut microbiomes are differently structured. An antagonistic interaction between the two biotic stressors was revealed with respect to survival when Daphnia, across all three genotypes, were exposed to the laboratory microbial inoculum, with a higher survival in the multiple stressor treatment than in the single stressor treatments. In contrast, no antagonistic interaction was detected in Daphnia exposed to a natural microbial inoculum, where the interaction effects were mainly host genotype-dependent. Our results provide the first causal evidence that host-stressor interaction patterns may be shaped by the gut microbiome and the uptake from certain strains from the environment. This raises concern that the many multiple stressor studies on lab-cultured animals with a differently structured microbiome may provide misleading results.